Ocean Acidification in the Arctic in a Multi-Regulatory, Climate Justice Perspective - Cassotta, Sandra (Frontiers in Climate, 2021)
The latest IPCC report on Ocean and Cryosphere in a Changing Climate, which builds upon previous IPCC’s reports, established a causal link between anthropogenic impacts and ocean acidification, by noting a significant decrease in the Ocean’s uptake of CO2, with consequent damage to Earth’s ecosystems, which in turn has traceable repercussions on the Arctic Ocean and then from the Arctic to the Planet Earth. The impact of ocean acidification is not only in the biological ecosystem but also on human activities, such as livelihood, food security, socio-economic security and developing communities. However, who can possibly be held ethically/legally responsible for ocean acidification from a climate justice perspective? Since what happens in the Arctic does not stay there, a more systematic law and policy approach to study options and responses in a multi-level, climate- ethical, global perceptive is needed. This paper sheds light on the legal responses available at global, regional and national levels to ocean acidification in a law of the sea and ocean context, both in the Arctic and from the Arctic. The gaps in legal and policy responses in connection to the ethical climate component will be identified. It will shed light on the planetary limits that humanity needs to stay within in order to maintain the future of the Earth. Since it touches upon questions of legal responsibility, on who is responsible for ocean acidification, it will connect to the “supply side” of fossil fuels production and global extraction projects causing anthropogenic CO2 emissions, one of the major causes of ocean acidification. It will also identify which actors, be they “officials” or “non-officials” (such as international organizations, states, regional institutes, Arctic citizens or even forums) should be held ethically responsible, and who should take action.